Susan ROTHSTEIN. Structuring Events: a study in the semantics of lexical aspect. Oxford: Blackwell ISBN 1-4051-0668-9 - Cunha, Luís Filipe (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
.